Evolution of multidimensional poverty in crisis-ridden Mozambique - Eva-Maria Egger; Vincenzo Salvucci; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Mozambique experienced important reduction in the poverty rate until recently, before two major natural disasters hit and the country started suffering from a hidden debt scandal with associated economic slowdown. As the last available national household expenditure survey is from 2014/15, just before these crises unfolded, there is need for a poverty assessment based on alternative data sources, especially since the COVID-19 crisis is now hitting the country. In this paper, we study the evolution of multidimensional poverty in Mozambique using the Demographic and Health Surveys/Malaria Indicator Survey data. Using both the standard Alkire-Foster multidimensional poverty index and the first-order dominance (FOD) method, we find that the poverty reduction trend observed between 2009-11 and 2015 halted between 2015 and 2018. Meanwhile, the number of poor people increased, mainly in rural areas and in the central provinces. Importantly, the poorest provinces did not improve their rankings over time, and between 2015 and 2018, no progress took place for most areas and provinces, as measured by the FOD approach.
Keywords: I32; 330; Mosambik; Mozambique; Demographic and Health Surveys Program; Data gathering